Postal system and circulation of correspondence during the first government of Juan Manuel de Rosas. Buenos Aires (1829-1832) (Quinto Sol, 2026)
In this article we analyze the process of circulation of correspondence through the post office system during the Juan Manuel de Rosas administration. We examine the first Rosas government, between 1829 and 1832, focusing on the institutional efforts aimed at boosting communication by reinforcing the structure of the existing postal system. In a second instance, we examine the government's attempts to homogenize this structure under the unanimist logic that the regime tried to impose in different spheres. Finally, and extending the temporal arc of the first Rosas government, we explore the circulation of correspondence during the 1833 expedition, when the federal leader was out of the management of political power in the province and arranged the configuration of a complex informal postal engineering. We consider that the practices of production, circulation and social reception of letters shaped a Rosas' epistolary culture that constituted one of the privileged spheres of communication during the regime.
Keywords: correspondence; postal system; circulation; relay system